HUBUNGAN ANTARA PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN INFEKSI SALURAN PERNAPASAN AKUT PADA BAYI USIA 4-6 BULAN DI POSYANDU KELURAHAN KADIPIRO SURAKARTA - Kusumawati, Etiek (2008)
Acute Respiratory Infection (ARI) represent the disease which still become the problem of health in Indonesia and become the cause of death of baby and children under five years old which high enough that is about 25% from death that happened. One of cause of height ARI at baby and children under five years old of because do not give of breastfeeding. This research aim to know the relation of between giving breastfeeding with the occurence of acute respiratory infection of age baby 4-6 month in Regional Posyandu Sub-District Kadipiro Surakarta. Research used by cross sectional. Methode of Intake of sampel random sampling with the technique of cluster random sampling summed uply is sampel research of counted 97 baby which have age to 4-6 month. Its his Free variable is giving breastfeeding and variable tied of occurence ARI. Analyse the data conducted by univariat and bivariate by chi square to know the relation of between free variable with the variable tied. Result of research obtained by 52,6% do not get the breastfeeding (non exclusive), and 47,4% getting breastfeeding, and also 74,2% do not suffer from the ARI and 25,9% suffering from ARI of where baby getting breastfeeding 40,2% attacked by ARI and 7,21% is not attacked by ARI. While at baby which is not given by the breastfeeding 18,56% ARI and 34,02 do not ARI. Result of this research show the r=-0,229 p=0,024 of where p≤0,05 Ho refused meaning there is relation of between giving breastfeeding with the occurence of disease ARI with negative relation. Recommend : so that health officer intensively can give the complete information to society specially baby mother of about its his important give the breastfeeding to prevent the infecting of ARI early on.